Desegregation state: college writing programs after the civil rights movement - Utah State University Press, publisher (Colorado State University. Libraries, 2022)
A history of federal enforcement of higher education desegregation and its impact on writing programs. Focusing on University System of Georgia and two colleges, one a historically segregated white college and a historically Black college showing desegregation enforcement promoted and shaped writing programs by presenting literacy remediation and testing as critical to desegregation.--Provided by publisher.
Mendenhall, Annie S.
"Technologies of This Theory": desegregation as remediation, early 1970s -- Assessing potential: writing placement as a retention strategy, mid-1970s -- Measures of control: writing programs and institutional identity, late 1970s -- "Who's the Villain?": writing assessment in desegregation policy, 1980s and beyond.
Keywords: College integration -- Georgia -- History -- 20th century; Writing centers -- Georgia; English language -- Rhetoric -- Ability testing -- Georgia; Reading -- Ability testing -- Georgia; African American college students -- Georgia; African Americans -- Education (Higher) -- Georgia